118k views
4 votes
Substitution Method
x+y=3
2x+y=7

2 Answers

5 votes

Answer:

6=7

Explanation:

User Tanisa
by
5.8k points
2 votes

Answer:

(4, - 1 )

Explanation:

Given the 2 equations

x + y = 3 → (1)

2x + y = 7 → (2)

Rearrange (2) expressing y in terms of x by subtracting 2x from both sides

y = 7 - 2x → (3)

Substitute y = 7 - 2x into (1)

x +7 - 2x = 3

7 - x = 3 ( subtract 7 from both sides )

- x = - 4 ( multiply both sides by - 1 )

x = 4

Substitute x = 4 into (3) for corresponding value of y

y = 7 - 8 = - 1

Solution is (4, - 1 )

User Mtl
by
5.5k points